(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background. One of the important areas of implementation of reversible holographic recording mediums (RMS) is their use in holographic interferometry, in particular, for non-destructive control and monitoring of physico-chemical and biological processes (defense topics, medicine, etc.). In some cases, the disadvantage of existing GRS is polychromaticity, which is why there is a need for protection from external exposure. Therefore, research is being conducted aimed both at expanding the spectral range of photosensitivity of such HMS and at creating selective HMS by structural modification of the corresponding chromophores, which leads to a change in the electronic structure of the system and an increase in the overall molecular mobility of chromophore groups. The purpose of the research was to obtain effective recording media for information technologies, development and creation of multifunctional photosensitive film polymer composites of various architectures and compositions, as effective photonics materials, in particular, materials of sensor systems in high technologies using holographic methods, as well as research of their spectral and informational properties. The objects of research are oligomeric compositions based on carbazolyl-, fluorenyl-, naphthyl- and anthracenyl-containing oligomers and co-oligomers doped with an ionic organic dye-sensitizer. Methods. UV-spectroscopy was used to determine the information characteristics of holographic recording media, and photoconductivity of films of oligomeric compositions were studied based on, in particular, the kinetics of the photocurrent under conditions of an alternating electric field. Results. It was established that the photoconductivity and photosensitivity of the created film recording media is higher in the case of co-oligomers containing links with different electron donation. It was concluded that the presence of terminal groups with different electron donation in co-oligomer films reduces the probability of oligomer molecules forming physical dimers and pre-dimer states, which are effective capture centers (traps) of photogenerated charge carriers, which leads to an increase in the photoconductivity of the corresponding film compositions and improvement their informational properties as recording media. Conclusions. Film-based reversible photothermoplastic holographic recording media based on films of carbazolyl-, fluore-nyl-, naphthyl-, and anthracenyl-containing oligomers and co-oligomers doped with an ionic organic sensitizer dye were created.